The Betimbang Tradition and the Construction of Religious Moderation in South Sumatra, Indonesia - Abdul Azis; Muslimin Muslimin; Gesit Yudha (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
This study examines the Betimbang tradition in South Indralaya District, Ogan Ilir Regency, South Sumatra Province, and its role in constructing religious moderation. The Betimbang is a communal tradition of mutual assistance during wedding receptions that has sparked debate between those who consider it excessive and contrary to Islamic teachings and others who maintain it as valuable local wisdom. This ethnographic study employed participant observation, in-depth interviews with community members and local religious leaders, and literature review to analyze the tradition's implementation and its relationship to religious moderation. The findings reveal that the Betimbang tradition functions as a mechanism for applying Islamic values of mutual assistance (ta'āwun) and social solidarity within extended family networks. Religious moderation is constructed through the integration of local cultural practices with Islamic teachings, facilitated by local religious leaders who provide contextual religious guidance during Betimbang ceremonies. This study contributes to the understanding of how local traditions can serve as vehicles for religious moderation by demonstrating the dynamic negotiation between cultural authenticity and religious orthodoxy in contemporary Indonesian Muslim communities.